Design of Automated PC Shutdown Control System in Coastal/LPI Radar System Based on Microcontroller ATMega8L - Fadil Habibi Danufane; Arief Nur Rahman; Eko Joni Pristianto (National Research and Innovation Agency, 2016)
One consideration during the design of long range controlled electrical system is the sudden outage of a Personal Computer (PC) caused by power failure. Frequent outage can damage the components inside the PC such that the whole system could be malfunction. This can affect the cost, time, and effort required to fix the system. Usually such system is equipped with a temporary power storage or UPS (uninterruptible power supply) with a small capacity, so the PC in the system can immediately be turned off before the UPS runs out. Therefore it is necessary to design a control system that can shutdown the PC automatically within a certain range of time after the outage. The implementation of designed system has used an ATmega8L microcontroller as a controller, an optoisolator PS2505-1 as isolator for electric components from AC signal, and Visual Basic as the programming language. The system has been tested with an input voltage of 220Vrms AC signal. The test result has shown that the PC was successfully shut down within a certain time range after the input was terminated.